Cavity dynamics of a hybrid mode‐locked figure of eight fiber laser. Issue 6 (11th March 2022) - Iqbal, Muddassir; Yuze, Wu; Youqiao, Ma; Ullah, Sibghat; Min, Lai; Delin, Zhao; Mao, Yaya
Abstract: Mode‐locking is an increased focus area due to the augmented requirement of ultra‐short and high‐intensity optical pulses for varied applications. Tunable mode‐locked lasers capable of operating in the infrared range at high repetition frequency brought innovative opportunities for insensitive and accurate laser surgery. As one important application of optical pulse propagation in an optical fiber, we have discussed a dual‐ring hybrid mode‐locked fiber laser using modulator, and saturable absorber. The active mechanism, saturable absorber, and the nonlinear optical loop mirror result in an output with a peak power of 16 dBm, and 80 fs full‐width at half‐maximum with a high duty cycle. It occupies a small space and is easy to achieve miniaturization and intensification; the laser output can be adjusted by varying multiple parameters such as pump, input, doped fiber length, modulator (including modulation signal), saturable absorber, and other devices.